2012
DOI: 10.1088/0964-1726/21/3/032002
|View full text |Cite
|
Sign up to set email alerts
|

Rate-dependent response of superelastic Cu–Al–Mn alloy rods to tensile cyclic loads

Abstract: We report the results of tensile cyclic loading tests conducted to examine the dependence of constitutive relations for superelastic Cu–Al–Mn alloy rods on loading rates. Recently, Cu–Al–Mn alloy rods with diameters up to 8 mm have been developed by the authors, and it has been demonstrated that these rods have excellent superelastic strains of more than 8%, which is comparable to Ni–Ti alloys and far superior to other Cu-based alloys. No information is available, however, on the rate dependence of constitutiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 34 publications
(15 citation statements)
references
References 32 publications
1
14
0
Order By: Relevance
“…Cu-based shape memory alloys have potential applications as seismic devices for energy absorption [42,43]. However, for these materials to be used in such applications it is necessary that the superelastic behaviour is stable for a wide range of temperatures [44], below −10°C and up to 50°C, ideally.…”
Section: Resultsmentioning
confidence: 99%
“…Cu-based shape memory alloys have potential applications as seismic devices for energy absorption [42,43]. However, for these materials to be used in such applications it is necessary that the superelastic behaviour is stable for a wide range of temperatures [44], below −10°C and up to 50°C, ideally.…”
Section: Resultsmentioning
confidence: 99%
“…These grain structures with a relatively large grain size are favorable for superelasticity. Another important factor is the crystallographic orientation because the transformation strain is greatly anisotropic in Cu-Al-Mn alloys (Araki et al, 2012). The crystallographic orientation of each grain in Specimens A, B, C and D is shown in Figure 6(b), where the solid and open circles show the orientation along the tensile loading direction of large and small grains, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…It is known, however, that the superelasticity of Cu-Al-Be alloys is about half that of Ni-Ti alloys. On the other hand, Araki et al (2012) investigated the rate dependency and superelastic performance of Cu-Al-Mn alloy bars of 8 mm diameter up to 1 Hz loading rate, and found that the rate-dependency was about 1/4 that of Ni-Ti alloys while superelasticity was comparable to Ni-Ti alloys (Araki et al, 2011). Sutou et al (2009) and Niitsu et al (2011) studied temperature dependency of Cu-Al-Mn wires of 1 and 2 mm diameter, respectively, and found that the temperature dependency was less than half that of Ni-Ti alloys.…”
Section: Introductionmentioning
confidence: 99%
“…The SMA utilising in this study is Cu-Al-Mn SMA provided by Shinko Metal Product Co., LTD, Japan. Araki et al [13] and Huang [14] stated that Cu-Al-Mn SMA has a large recovery strain and fracture strain, and the low-cycle fatigue of Cu-Al-Mn SMA was found to be superior. According to Araki et al [15], copper-based SMA is less expensive than NiTi SMA, and the Cu-Al-Mn alloy is the cheapest and even more inexpensive than other copper-based SMAs.…”
Section: Materials Study Of Sma 21 Methodsmentioning
confidence: 99%